Modelling with AutoCAD : Release 13 for Windows / Robert McFarlane. - McFarlane, Robert (Arnold, 1997)
This guide is intended to take the CAD user familiar with 2D work on to the more stimulating challenges of 3D modelling, and will be valuable to students on a range of further and higher education CAD courses.